2021
DOI: 10.1007/s43477-021-00023-2
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Context in General and Special Education: An Exploratory Investigation to Describe the Perspective of School Leaders

Abstract: Organizational context (e.g., climate, culture, resources) can impede or enhance implementation of evidence-based practices in general education settings or special education settings serving students with autism spectrum disorder. We examined the relations between organizational context and individual (i.e., implementation leadership, administrator- or service provider-role) or school (i.e., enrollment size, public/nonpublic school type) characteristics. Participants were administrative or service providing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…Little is known about predictors of better or worse implementation climate or leadership in schools: some studies suggest that school demographics (such as racial composition, percentage of special education students, and school size) have a negligible effect on schools' ability to support EBP implementation (Lyon et al, 2022;Thayer et al, 2022), while others suggest potential differences in the inner context due to school location or size (Moore et al, 2021;Suhrheinrich et al, 2021). In terms of linkages between strategic organizational factors and EBP implementation, studies have found mixed support in clinical settings (Meza et al, 2021;Powell et al, 2021) as well as in schools.…”
Section: Strategic Organizational Factors To Implement Evidence-based...mentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about predictors of better or worse implementation climate or leadership in schools: some studies suggest that school demographics (such as racial composition, percentage of special education students, and school size) have a negligible effect on schools' ability to support EBP implementation (Lyon et al, 2022;Thayer et al, 2022), while others suggest potential differences in the inner context due to school location or size (Moore et al, 2021;Suhrheinrich et al, 2021). In terms of linkages between strategic organizational factors and EBP implementation, studies have found mixed support in clinical settings (Meza et al, 2021;Powell et al, 2021) as well as in schools.…”
Section: Strategic Organizational Factors To Implement Evidence-based...mentioning
confidence: 99%
“…Of the various conditions for EBP adoption studied in implementation science, one topic that requires further study in school settings are “inner-context” implementation factors ( Locke, Lawson, et al, 2019 ; Lyon & Bruns, 2019 ), as described in various implementation frameworks, including the Exploration, Preparation, Implementation, Sustainment (EPIS) framework ( Aarons et al, 2011 ). Inner-context factors of organizations implementing EBPs, including provider attitudes and organizational strategic context, have been shown to be influential for EBP implementation ( Aarons et al, 2009 ; Moullin et al, 2019 ; Sijercic et al, 2020 ). While these factors have been studied frequently in clinical healthcare settings, more studies are needed to understand their mechanisms when scaled out to non-specialty settings like schools ( Aarons, Sklar, et al, 2017 ; Wolk et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…One factor that may impact EBP implementation in schools is the structure of the special education system and the limited capacity most state systems have for scaling up EBPs ( IDEA, 2004 ). There is some evidence of differences in leader perceptions of culture and climate between general and special education ( Moore et al, 2021 ). This may be because special education has a more distributed leadership structure than general education with less authority at the school site level and more at the centralized district level.…”
Section: Introductionmentioning
confidence: 99%